Proceedings of COMPSTAT'2010 19th International Conference on Computational StatisticsParis France, August 22-27, 2010 Keynote, Invited and Contributed Papers - Lechevallier, Yves.; Saporta, Gilbert; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2010)
Proceedings of the 19th international symposium on computational statistics, held in Paris august 22-27, 2010.Together with 3 keynote talks, there were 14 invited sessions and more than 100 peer-reviewed contributed communications.
Part I: Keynote -- Part II: ABC Methods for Genetic Data -- Part III: Algorithms for Robust Statistics -- Part IV: Brain Imaging -- Part V: Computational Econometrics -- Part VI: Computer-Intensive Actuarial Methods -- Part VII: Data Stream Mining -- Part VIII: Functional Data Analysis -- Part IX: Kernel Methods.-Part X: Monte Carlo Methods in System Safety, Reliability and Risk Analysis -- Part XI: Optimization Heuristics in Statistical Modelling -- Part XII: Spatial Statistics / Spatial Epidemiology -- Part XIII: ARS Session (Financial) Time Series -- Part XIV: KDD Session: Topological Learning -- Part XV: IFCS Session: New Developments in Two or Highermode Clustering; Model Based Clustering and Reduction for High Dimensional Data -- Part XVI: Selected Contributed Papers -- Part XVII: E-supplementary material: Contributed Papers.
Keywords: Statistics; Mathematical statistics; Statistics; Statistics and Computing/Statistics Programs